The role of the transfusion practitioner in the multidisciplinary team. (10th January 2018) - Bielby, L.; Haberfield, A.; Kelsey, G.; Kay, S.
Abstract : Background: Transfusion and patient blood management (PBM) processes are complex; while transfusions can be life‐saving, equally there may be associated morbidity and mortality. In Australia, obligations to comply with mandatory governance frameworks have propelled the safety and PBM culture. These frameworks support appropriate product use and levels of safety at all points of the process. Methods: A key to blood management governance success is the multidisciplinary Blood Management team/Governance Committee. This team includes healthcare executive, clinical governance, consumer/s and medical/laboratory/nursing representatives, with the transfusion practitioner (TP) as a key resource. The TP is often seen as the driving force for change, working in a multidisciplinary capacity across the clinical spectrum. In Australia, this influence can be within an individual organization, across multiple sites/networks, in metropolitan or rural/regional areas. The TP conducts a critical role pulling together resources, promoting exchange of information, encouraging engagement and empowering colleagues to facilitate change. Highly developed communication skills assist the TP to engage these many different stakeholders and clinical environments. Collaboration is essential for the multidisciplinary team to function effectively. Highly functional teams recognize knowledge and experience and utilize each member's skills to work together to deliver the best possible outcome for patients. There is a growing body of literature supporting multidisciplinary teams and the TP role improving patient outcomes. Conclusion: Effective transfusion and PBM practice require a systematic cross‐specialty approach to ensure success. TPs are an essential link in the multidisciplinary chain and require strong support and leadership to potently effect change and enhance practice.